PENGARUH PROMOSI PENJUALAN DAN KUALITAS LAYANAN TERHADAP MINAT BELI ULANG MELALUI KEPUASAN PELANGGAN PADA STARBUCKS COFFEE GRAND WISATA BEKASI - Candra Dwi Hardiana; Francois Romario Kayadoe (Jurnal Ekonomi dan Bisnis, 2022)
This study aims to analyze the effect of Sales Promotion and Service Quality on Repurchase Intention through customer satisfaction Starbucks Coffee Grand Wisata Bekasi. The sampling technique used accidental sampling so that the population in this study was not all sampled, in this study the population is visitors to Starbucks Coffee Grand Wisata Bekasi are making a purchase and the sample was 160 respondents. The analytical method used is Structural Equation Modeling (SEM) with the PLS (Partial Least Squares) approach. Data analysis using the WarpPLS version 5.0 program. In general, the results of the analysis show Sales Promotion and Service Quality have a positive and significant effect on Customer Satisfaction and Repurchase Intention with the beta coefficient being positive and resulting in a significance of <0.05 (α 5%). The mediation analysis in this study resulted in the conclusion that Sales Promotion had a significant effect on Repurchase Intention trough Customer Satisfaction , and Service Quality had a significant effect on on Repurchase Intention trough Customer Satisfaction.